Influências da ética e da religiosidade no enfrentamento da culpa em situação de consumo moral - Murtinho, Max Nunes (2019)
The main objective of the Thesis was to advance the understanding of Coping in Consumer Behavior, developing a conceptual model and testing it empirically. In order to reach the main objective, two specific objectives were defined: a) analysis of how Deontological and Teleological Ethics Influence Facing Consumer Guilt in Situation of Moral Consumption [Study 1]; b) analysis of how much Consumer Religiosity - Intrinsic and Extrinsic Religiosities - Influence Facing Consumer Guilt in Situation of Moral Consumption [Study 2]. The structure of the proposed Conceptual Model incorporates the dual nature of Psychological Stress Facing (Byrne, 1964, Miller, 1987, Mullen & Suls, 1982) and the non-exclusionary character of the Coping proposed by Krohne (1989). Therefore, in this thesis, the dependent variables of Studies 1 and 2, which represent the duality of Guilt Coping, are the Consumer and Evasive Behavior. In relation to the methodological procedures, the Chi-Square Test and the Frequency Distribution were used between the variables of each hypothesis. A validation process of the Scale Facing Coping in Situation of Moral Consumption was carried out. The results point to an influence of Ethics and Religiosity in Coping Consumer Guilt. Considering the situation of Moral Consumption, Study 1 demonstrated that the predominance in Deontological Ethics is capable of promoting a tendency for the choice of Reparative Behavior as a predominant Coping. In the same way, the consumer in whom Teleological Ethics predominates will tend to react to Blame by means of Evasive Behavior. In Study 2, an influence of the individual's Religiosity in the Guilt Coping is evidenced. This time, when Intrinsic Religiosity predominates in the individual, the individual will tend to react predominantly in Repairing Behavior, when Extrinsic Religiosity predominates, tends towards Evasive Behavior.